The Influence of Internal Control System and HR Competence on the Quality of Financial Reports of PT. Bank Perkreditan Rakyat Mangatur Ganda - Dandi Sianipar; M. Irsan Nasution (Universitas 17 Agustus 1945 Semarang, 2025)
This study is entitled